Everyday biblical literacy : the essential guide to biblical allusions in art, literature, and life - Lang, J. Stephen (Cincinnati, Ohio : Writer's Digest Books, 2007)
This book is a compilation of the most important people, places, and phrases mentioned in the Bible.
Includes index.
Keywords: Bible -- Dictionaries